Training loads and heart rate variability of young skiers - Anpilogov I.E.; Pavlov P.V. (Theory and Practice of Physical Culture, 2024)
Abstract Objective of the study was to evaluation of the changes in the relationships and fluctuations between the indicators of heart rate variability in young skiers during a training session. Methods and structure of the study. Heart rate variability was assessed in 12 mass-class skiers aged 13,2±0,4 years using the MS FIT system (Medicalsoft, RF) before and after exercise in a sitting position. The training load was a cross-country run with an imitation of an uphill run alternating with running. Five series of 10 repetitions of an uphill run of 150 m with a slope of 7-9º were performed. Results and conclusions. The correlation between the indicators of the heart muscle’s performance undergoes a substantial transformation under the influence of physical exertion. The assessment of athletes’ functional status and their performance solely based on quantitative HRV data, without considering the evolution of the correlation, can result in an erroneous interpretation of the findings.